Effects of Distilled Cervi Pantotrichum Cornu and Rehmannia glutinosa Pharmacopuncture at GB21 (Jianjing) on Heart Rate Variability: A Randomized and Double-blind Clinical Trial - Young-Joo Kim; Chang-Hyun Lee; Jong-Uk Kim; Tae-Han Yook (Medical Association of Pharmacopuncture Institute, 2016)
Background/Purpose: The purpose of this study was to use heart rate variability (HRV) to investigate the effects of distilled Cervi Pantotrichum Cornu pharmacopuncture and Rehmannia glutinosa pharmacopuncture on the autonomic nervous system. Materials and methods: Forty healthy male participants were divided into two groups: the participants of the C-group received distilled Cervi Pantotrichum Cornu pharmacopuncture and those of the R-group received Rehmannia glutinosa pharmacopuncture. The study design was a randomized, double-blind clinical trial. Each participant received one of the two solutions injected at GB21 (Jianjing). The changes in HRV were measured seven times using the QECG-3: LXC3203 system (LAXTHA Inc. Korea). Time-dependent changes in HRV for each group were analyzed using the paired t test (significance level: p < 0.05), and the difference in the HRV fluctuations between the two experimental groups was evaluated using the independent sample test (significance level: p < 0.05). Results and conclusion: The results showed that Cervi Pantotrichum Cornu pharmacopuncture and Rehmannia glutinosa pharmacopuncture tended to activate the autonomic nervous system within the normal range. Cervi Pantotrichum Cornu pharmacopuncture tended to activate the sympathetic nervous system, whereas Rehmannia glutinosa pharmacopuncture tended to activate both the sympathetic and parasympathetic nervous systems.